Implementation of interfaith tolerance learning design for senior high school students in Bandung - Mulyani, Qori; Tarsono, Tarsono (Universitas Pendidikan Indonesia, 2022)
Abstract. The issue of tolerance will always be present in a heterogeneous society. The values of tolerance must continue to be instilled in the community, including through educational institutions. This study examines the application of interfaith tolerance learning designs for high school students in the city of Bandung. This study uses a qualitative approach and descriptive method. The data collection technique used library studies. Data analysis is carried out by crystallizing theories from various disciplines that support the formation of learning designs. The results show that the interfaith tolerance learning design can be applied to high school students.